Characterization and hydrothermal synthesis of nanocrystalline α-Fe2O3 with different morphologies. (4th July 2018) - Zhou, Ying; Yu, Longlong; Xie, Xinyu; Tang, Peisong; Chen, Haifeng
ABSTRACT: The nanocrystalline α-Fe2 O3 was prepared using ferric(III) chloride and sodium hydroxide by a hydrothermal process. The effects of hydrothermal reaction temperature and time, concentration of sodium hydroxide on the morphology of α-Fe2 O3 were studied. The prepared α-Fe2 O3 products were characterized by powder X-ray diffraction (XRD) and scanning electron microscopy (SEM). The results show that hydrothermal reaction temperature and time, concentration of sodium hydroxide have all effects on morphology of α-Fe2 O3 . When hydrothermal reaction temperature is raised from 140°C to 200°C, the morphologies of α-Fe2 O3 samples are gradually converted from a needle-like mixture to a single flaky. When hydrothermal reaction time increased from 8 h to 24 h, the morphologies of α-Fe2 O3 samples gradually changed from grain to flaky. And when concentration of sodium hydroxide increased from 1 mol/L to 6.5 mol/L, the morphologies of α-Fe2 O3 samples changed from quasi-cubic to sheet.